Peran Guru dalam Mengembangkan Keterampilan Sosial Anak Dimasa Pandemi Covid-19 Pada Kelompok B di TK Nusa Indah Toto Utara - Irvin Novita Arifin; Setiyo Utoyo; Evita Paputungan (Early Childhood Education Department, Faculty of Education, State University of Gorontalo, 2023)
The purpose of this study was to determine the teacher's role in developing children's social skills during the Covid-19 pandemic in group B at the North Nusa Indah Toto Kindergarten, Tilongkabila District, Bone Bolango Regency. This type of research uses a qualitative descriptive approach. From the results of the study it can be seen that the teacher's role in developing children's social skills during the Covid 19 pandemic in group B at Nusa Indah Toto North Kindergarten, Tilongkabila District, Bone Bolango Regency was carried out through five roles, namely the teacher's role as a guide, informator, class manager, facilitator, and communicator well done. The role of the teacher as a facilitator is carried out by the teacher providing facilities that allow for the convenience of children's learning activities, the role of the teacher as a communicator is carried out by the teacher being a friend, or a child's confidant when the child is having problems at home.